Boron-containing carbon material, resin composition, and conductive film

A boron-doped carbon material with controlled boron content and thermal stability addresses the conductivity and oxidation resistance issues, providing enhanced performance in conductive films and compositions.

JP7605010B2Active Publication Date: 2024-12-24TOYO INK MFG CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021075215
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-27
Filing Date
2021-04-27
Publication Date
2024-12-24
Estimated Expiration
2041-04-27

AI Technical Summary

Technical Problem

Conductive carbon materials lack sufficient conductivity and oxidation resistance, limiting their use in conductive applications, and existing composites with carbon and silicon carbide compromise conductivity for improved oxidation resistance.

Method used

A boron-containing carbon material is developed with a thermal decomposition temperature of 700°C or more and less than 1000°C, containing 0.005 to 15 mol% boron, which enhances conductivity and oxidation resistance by improving carrier density and maintaining mobility.

Benefits of technology

The boron-containing carbon material achieves excellent conductivity and oxidation resistance, suitable for conductive films and compositions, with improved dispersibility and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605010000003
    Figure 0007605010000003
  • Figure 0007605010000001
    Figure 0007605010000001
  • Figure 0007605010000002
    Figure 0007605010000002
Patent Text Reader

Abstract

To provide a boron-containing carbon material having excellent oxidation resistance and electrical conductivity by realizing a boron-containing carbon material having excellent oxidation resistance and electrical conductivity.SOLUTION: A boron-containing carbon material in which boron elements are doped to replace at least a part of the carbon elements in a carbon skeleton, a thermal decomposition temperature in an oxygen atmosphere is 700°C or more and less than 1,000°C, and the boron element content in the carbon material is 0.005-15 mol%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a boron-containing carbon material, a resin composition, and a conductive film. [Background technology]

[0002] In recent years, electronics has developed remarkably, and conductive materials used in various electronic devices are also required to be smaller and lighter, to be less expensive, and to have a longer life under various usage environments. For example, when manufacturing the wiring for electronic device substrates or wiring for connecting electronic devices, a conductive composition with good conductivity is required, but conductive compositions using metal fillers such as silver and copper are generally used, and major issues such as cost and durability have yet to be resolved. On the other hand, various studies have been conducted on conductive compositions using conductive carbon materials that do not use metals, but due to insufficient conductivity, their use has been limited to semi-conductive applications such as antistatic applications.

[0003] As conductive carbon materials, highly conductive carbons such as graphite and carbon nanotubes have been considered. The volume resistivity of these highly conductive carbons is 10 -2 It has been reported that it has a conductivity of about Ω·cm, and can improve the issue of conductivity compared to conventional methods (Patent Document 1). However, the volume resistivity of the material itself is an order of magnitude higher than that of metal fillers, and it is difficult to say that conductive carbon alone exhibits sufficient properties for conductive applications.

[0004] On the other hand, carbon materials such as graphite are suitable for use at high temperatures due to their thermal stability, and are suitable as materials for aerospace and semiconductor manufacturing applications. However, carbon materials are easily oxidized in a high-temperature oxygen atmosphere, and there are concerns about the effects of oxidative decomposition and the like that result. In order to suppress the effects of this oxidation, the development of a composite with improved oxidation resistance by combining carbon and silicon carbide has been reported (Patent Document 2). However, with this method, the conductivity of carbon is inhibited by the mixed material, making it difficult to achieve both conductivity and oxidation resistance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-105208 A [Patent Document 2] JP 2000-351672 A Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above problems, an object of the present invention is to provide a boron-containing carbon material having excellent oxidation resistance and electrical conductivity, thereby providing a material having excellent oxidation resistance and electrical conductivity. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above-mentioned problems and have arrived at the present invention. That is, the present invention relates to a boron-containing carbon material doped with boron element so as to substitute at least a portion of the carbon element in the carbon skeleton, the boron-containing carbon material having a thermal decomposition temperature in an oxygen atmosphere of 700°C or higher and lower than 1000°C, and a content of boron element in the carbon material of 0.005 to 15 mol%.

[0008] The present invention also relates to the above boron-containing carbon material, wherein the content of boron element on the surface of the carbon material is 0.01 to 10 mol %.

[0009] The present invention also relates to the above boron-containing carbon material, which contains at least one material selected from the group consisting of graphite-based carbon materials, graphene-based carbon materials, and carbon nanotube-based carbon materials.

[0010] The present invention also relates to the above boron-containing carbon material, wherein the content of boron element on the surface of the carbon material is 0.01 to 1 mol %.

[0011] The present invention also relates to the above boron-containing carbon material, which has a thermal decomposition temperature in an oxygen atmosphere of 800°C or higher and lower than 900°C.

[0012] The present invention also relates to a resin composition containing the above carbon material and a resin component.

[0013] The present invention also relates to the above resin composition further comprising a conductive assistant.

[0014] In addition, the present invention provides a conductive assistant having a pore volume of 0.1 to 5 cm 3 / g.

[0015] The present invention also relates to a conductive film formed from the above resin composition. Effect of the Invention

[0016] According to the present invention, it is possible to provide a boron-containing carbon material having excellent electrical conductivity and oxidation resistance. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 shows an example of a TG curve and a DTA curve in TG-DTA, and a thermal decomposition temperature.

[0018] The present invention will be described in detail below. In this specification, the term "boron-containing carbon material" may be simply referred to as a carbon material.

[0019] <Boron-containing carbon materials> A boron-containing carbon material that is doped with boron to replace at least a portion of the carbon elements in the carbon skeleton is a carbon material that has a basic skeleton of a hexagonal carbon mesh surface in which carbon atoms are covalently bonded in a hexagonal mesh pattern to form a mesh plane, has physical and chemical interactions (bonds) between these constituent units, is doped with boron to replace at least a portion of the carbon elements, and may contain hetero elements such as nitrogen and nitrogen elements, or base metal elements.

[0020] The content of boron element in the boron-containing carbon material (the content of boron in the entire carbon material) is 0.005 to 15 mol%, preferably 0.01 to 10 mol%, and more preferably 0.08 to 5 mol%. If the content of boron is less than 0.005 mol%, the boron doping effect is not obtained and the conductivity is not improved, and if the content of boron is 15 mol% or more, the excess boron inhibits the movement of electrons and the conductivity decreases, so if the content is in the range of 0.005 to 15 mol%, good conductivity can be exhibited. In addition, the boron-containing carbon material contains boron, which increases wettability with respect to solvents and binder resins, improving the dispersibility of the dispersion. In addition, a high boron content tends to increase the hardness of the carbon material, improving durability against external forces such as impacts, thereby improving dispersion stability and film strength. On the other hand, a high boron content tends to make dispersion difficult, so from the viewpoint of the strength and dispersibility of the carbon material, the boron content is preferably 2 mol% or less, more preferably 1 mol% or less. The content of boron in the boron-containing carbon material can be determined by a method such as ICP emission spectrometry or ICP mass spectrometry. An example is a measurement method in accordance with JIS-R7223. The form of boron in the boron-containing carbon material is not particularly limited. For example, substitutional boron element (BC3 type) in which a boron element is substituted at the position of a carbon element in a carbon skeleton, boron carbide type and boron cluster type boron element (B4C type, Bc type), boron oxide type boron element in a completely or partially oxidized state (BC2O type, BCO2 type, B2O3 type), etc. can be mentioned.

[0021] The boron-containing carbon material preferably has a boron element content of 0.01 to 10 mol% atm%, more preferably 0.01 to 1 mol%, and even more preferably 0.05 to 0.6 mol% on the surface of the carbon material. When the proportion of boron element is 0.01 to 10 mol%, a carbon material with excellent electrical conductivity and oxidation resistance can be obtained. The boron element content on the surface of the carbon material can be measured by a method such as X-ray photoelectron spectroscopy (XPS).

[0022] In addition, the ratio of substitutional boron elements (BC3 type) on the surface of the boron-containing carbon material measured by X-ray photoelectron spectroscopy (XPS) is preferably 0.01 to 6 mol%, more preferably 0.01 to 1 mol%, and even more preferably 0.01 to 0.4 mol%. Since the substitutional boron elements (BC3 type) have the effect of improving carrier density, a carbon material with excellent electrical conductivity can be obtained. The ratio of substitutional boron elements on the surface of the carbon material is defined as the ratio B of the spectral area of ​​all boron elements to the spectral area of ​​all elements on the carbon material surface measured by XPS, and the ratio of the peak area of ​​substitutional boron elements to the spectral area of ​​all boron elements on the carbon material surface obtained from the B1s spectrum of XPS is defined as B. R Then, B×B R It is expressed as:

[0023] The B1s spectrum of boron obtained by XPS measurement appears in the binding energy range of the B1s electron of boron element (around 185 to 197 eV), and is known to be roughly divided into four components. The binding energy values ​​(peak tops) of each component are 186 to 187 eV for boron clusters, 187 to 188 eV for boron carbide, 188 to 189.3 eV for boron doped to replace carbon elements with a hexagonal mesh surface as the basic skeleton (BC3), 189.5 to 190.5 eV for various boron oxides BC2O, 191.5 to 192 eV for BCO2, and 192.5 to 193 eV for B2O3. When these peaks overlap, the ratio can be determined by fitting each component as a Gaussian function, optimizing the peak intensity, peak position, and full width at half maximum as parameters, and separating the peaks. Therefore, the state of boron on the surface of the boron-doped carbon material can be analyzed by performing peak separation of B1s.

[0024] The electrical conductivity of the boron-containing carbon material is expressed by the following formula. σ=μ×n×e (Equation 1) μ: mobility, n: carrier density, e: elementary charge (constant) From the above formula (1), it is necessary to improve the mobility and / or carrier density in order to improve the electrical conductivity. By doping a carbon material with boron, the carrier density is improved. On the other hand, doping a carbon material with boron has a large effect on the crystal structure and electronic state of carbon, and depending on the doping state such as the amount of doping and the doping location, it may induce a disorder in the crystal structure of carbon, which may cause a decrease in the oxidation resistance and mobility of carbon. Therefore, by doping with boron element and maintaining high oxidation resistance, it is possible to increase the carrier density while suppressing the decrease in mobility, and it is believed that high electrical conductivity can be expressed.

[0025] The boron-containing carbon material is not particularly limited, and examples thereof include graphite-based carbon materials, carbon nanotube-based carbon materials, graphene-based carbon materials, carbon black-based carbon materials, etc. From the viewpoint of the oxidation resistance of the boron-containing carbon material, graphite-based carbon materials, carbon nanotube-based carbon materials, and graphene-based carbon materials are preferred.

[0026] The thermal decomposition temperature of the boron-containing carbon material in an oxygen-containing atmosphere is 700° C. or more and less than 1000° C., and preferably 800° C. or more and less than 900° C. If it is 1000° C. or more, the contribution of impurities other than substituted boron increases, resulting in a decrease in electrical conductivity, and if it is less than 700° C., the crystallinity of the carbon material is low, resulting in a decrease in electrical conductivity and durability. If the thermal decomposition temperature is 800° C. or more and less than 900° C., the hardness of the carbon material tends to increase, and durability against external forces such as impacts is improved, resulting in improved dispersion stability and film strength.

[0027] The thermal decomposition temperature of the present invention can be determined by TG-DTA (Thermogravimetry-Differential Thermal Analysis) measurement. Specifically, a TG curve and a DTA curve are obtained by performing a TG-DTA measurement under air flow conditions. The rise of the largest exothermic peak (A in FIG. 1) and the top of the largest exothermic peak (B in FIG. 1) in the obtained DTA curve are read, and the intersection point (C in FIG. 1) extrapolated from the slope at the corresponding points (A', B' in FIG. 1) of the TG curve is determined as the thermal decomposition temperature.

[0028] The average particle size of the boron-containing carbon material in the present invention is preferably 0.01 to 1000 μm, and more preferably 0.1 to 200 μm. The average particle size is the particle size (D50) at which the volume ratio of particles is 50% when the volume ratio of particles is accumulated from the finest particle size in the volume particle size distribution, and is measured with a general particle size distribution meter, for example, a dynamic light scattering particle size distribution meter ("Microtrac UPA" manufactured by Nikkiso Co., Ltd.). The particle thickness is preferably greater than 50 nm. More preferably, it is greater than 100 nm. More preferably, it is 250 nm or more. The boron-containing carbon material of the present invention is highly crystalline, and larger particles are preferable because they are advantageous for electronic conductivity. The particle thickness of the boron-containing carbon material can be calculated from the average thickness of randomly sampled particles, for example, using an electron microscope.

[0029] <Manufacturing method> The method for producing the boron-containing carbon material of the present invention is not particularly limited, but is preferably a method including a step of mixing a carbonaceous raw material with a compound containing boron, and a step of heat-treating the mixture at a high temperature of 1000° C. or more. A preferred method for producing the boron-containing carbon material of the present invention is a method in which a carbon source that has been carbonized in advance is doped with boron. The term "carbonization" used here refers to a phenomenon similar to "crystallization" or "graphitization." For example, in a method of obtaining a boron-containing carbon material by doping boron while carbonizing a non-carbonized carbon source and a boron source, or a method of using a carbon source that has been pre-calcined, crystallization or graphitization may be insufficient. For this reason, it is preferable to use a method of performing a boron doping reaction after carbonization, such as doping boron into a carbon source that has been carbonized in advance, rather than a method of doping boron while carbonizing, because it is possible to produce a carbon material with a favorable distribution state of boron on the surface and inside of the carbon particles. In other words, in order to obtain the boron-containing carbon material of the present invention that can achieve both excellent oxidation resistance, electrical conductivity, dispersibility, and durability, the selection of the carbon source and the mixed state of the carbon source and the boron source when the boron doping reaction occurs are also important.

[0030] The raw material composition ratio of the carbonaceous raw material and the boron-containing compound for producing a boron-containing carbon material is not particularly limited, but the ratio of the boron-containing compound to 100 parts by mass of the carbonaceous raw material is preferably 0.01 to 300 parts by mass, and more preferably 0.1 to 100 parts by mass.

[0031] The method for preparing the mixture may include at least a carbonaceous raw material and a compound containing boron, and examples of the mixing method include dry mixing and wet mixing. As a mixing device, the following dry mixing device or wet mixing device can be used.

[0032] Examples of dry mixing devices include roll mills such as two-roll and three-roll devices, high-speed agitators such as Henschel mixers and super mixers, fluid energy pulverizers such as Micronizers and jet mills, attritors, particle composite devices manufactured by Hosokawa Micron Corporation such as "Nanocure," "Nobilta," and "Mechanofusion," and powder surface modification devices manufactured by Nara Machinery Manufacturing Co., Ltd. such as "Hybridization System," "Mechano Micros," and "Miraro."

[0033] In addition, when using a dry mixer, two or more raw materials may be directly mixed in powder form, but in order to prepare a more uniform mixture, one or more raw materials may be dissolved or dispersed in a small amount of solvent beforehand and then mixed. In order to further increase the processing efficiency, heating may be used.

[0034] Examples of wet mixing devices include mixers such as Disper, Homomixer, or Planetary Mixer, homogenizers such as M-Technique's "Clearmix" or PRIMIX's "Filmix", Red Devil's paint conditioner, ball mill, sand mills such as Shinmaru Enterprises' "Dynomill", attritor, or Coball Mill, media-type dispersers, wet jet mills such as Genus PY, Sugino Machine's "Starburst", Nanomizer's "Nanomizer", media-less dispersers such as M-Technique's "Clear SS-5" or Nara Machinery's "Micros", or other roll mills, kneaders, etc., but are not limited thereto. In addition, it may be preferable to use a wet mixing device that has been treated to prevent metal from entering the device.

[0035] For example, when using a media type disperser, it is preferable to use a method using a disperser whose agitator and vessel are made of ceramic or resin, or a disperser whose metallic agitator and vessel surface are treated with tungsten carbide spraying, resin coating, or the like. As the media, it is preferable to use ceramic beads such as glass beads, zirconia beads, or alumina beads. Also, when using a roll mill, it is preferable to use a ceramic roll. Only one type of dispersing device may be used, or multiple types of devices may be used in combination.

[0036] Furthermore, when the raw materials are not uniformly dissolved in the system, a general dispersant may be added together to disperse and mix the raw materials in order to improve the wettability and dispersibility of each raw material in the solvent.

[0037] As for the dispersant, the dispersant used in the present invention functions effectively as a dispersant for each raw material and can alleviate the aggregation. As long as it has the effect of alleviating aggregation, there is no particular limitation, and any dispersant known in the art can be used. For example, dispersants such as resin-type dispersants, surfactants, and pigment derivatives can be used.

[0038] Examples of the resin-type dispersant include polyvinyl resins, polyurethanes, polyesters, polyethers, cellulose resins such as carboxymethyl cellulose, formalin condensates, silicones, and composite polymers thereof. Furthermore, two or more of these resin-type dispersants may be used in combination. Polyvinylpyrrolidone, polyvinyl alcohol, polystyrene sulfonic acid, polyacrylic acid, carboxymethyl cellulose, etc. are preferred.

[0039] In the method of heat treating the mixture, the heating temperature is preferably 1000 to 3200°C, more preferably 1800 to 3000°C, although it varies depending on the types and amounts of the carbonaceous raw materials and the boron-containing compound used as raw materials.

[0040] The heating time is not particularly limited, but is usually preferably from 30 minutes to 10 hours.

[0041] Regarding the atmosphere in the heat treatment step, in order to prevent oxidation of the raw materials, an inert gas atmosphere such as nitrogen or argon, or a vacuum atmosphere is preferable.

[0042] In addition, the heat treatment process is carried out in one step under a certain atmosphere and temperature. It is also possible to carry out the reaction in multiple stages by changing the atmosphere or temperature each time.

[0043] <Carbon-based raw materials> In the present invention, the carbon-based raw material for producing the boron-containing carbon material is preferably an inorganic carbon-based raw material. Specific examples of the inorganic carbon-based raw material include carbon black (furnace black, acetylene black, ketjen black, medium thermal carbon black), activated carbon, graphite, carbon nanotubes, carbon nanofibers, carbon nanohorns, graphene, graphene nanoplatelets, nanoporous carbon, carbon fibers, and charcoal. Among the above carbon-based raw materials, the size and lamination structure of the carbon hexagonal mesh surface vary depending on the type and manufacturer, and the crystallinity, particle size, shape, BET specific surface area, pore volume, pore size, bulk density, DBP oil absorption, surface acid-basicity, surface hydrophilicity, conductivity, and other physical properties and costs vary, so that the optimal material can be selected according to the application and required performance.

[0044] Examples of commercially available carbonaceous raw materials include graphite manufactured by Nippon Graphite Industries Co., Ltd., such as CMX, UP-5, UP-10, UP-20, UP-35N, CSSP, CSPE, CSP, CP, CB-150, CB-100, ACP, ACP-1000, ACB-50, ACB-100, ACB-150, SP-10, SP-20, J-SP, SP-270, HOP, GR-60, LEP, F#1, F#2, and F#. 3. CGC-20, CGC-50, CGB-20, CGB-50, PAG-60, PAG-80, PAG-120, PAG-5, HAG-10W, HAG-150, etc., EC1500, EC1000, EC500, EC300, EC100, EC50, etc. manufactured by Ito Graphite Industries, CX-3000, FBF, BF, CBR, SSC-3000, SSC-600, SSC-3, SSC, CX-60 manufactured by Chuetsu Graphite 0, CPF-8, CPF-3, CPB-6S, CPB, 96E, 96L, 96L-3, 90L-3, CPC, S-87, K-3, CF-80, CF-48, CF-32, CP-150, CP-100, CP, HF-80, HF-48, HF-32, SC-120, SC-80, SC-60, SC-32, RA-3000, RA-15, RA-44, GX-600, G-6S, G-3, G-150, G- 100, G-48, G-30, G-50, SGP-100, SGP-50, SGP-25, SGP-15, SGP-5, SGP-1, SGO-100, SGO-50, SGO-25, SGO-15, SGO-5, SGO-1, SGX-100, SGX-50, SGX-25, SGX-15, SGX-5, SGX-1 and the like manufactured by SEC Carbon Co., Ltd., and 10099M and PB-99 manufactured by Nishimura Graphite Co., Ltd. Commercially available carbon blacks include Ketjenblack EC-300J, EC-600JD, and Lionite EC-200L manufactured by Lion Specialty Chemicals. Examples of the black pigment include Furnace Black #2350, #2600, #3050B, #3030B, #3230B, and #3400B manufactured by Mitsubishi Chemical Corporation, and Denka Black HS-100 and FX-35 manufactured by Denka Company. Commercially available carbon nanotubes include VGCF-H and VGCF-X manufactured by Showa Denko Co., Ltd. Examples of the nanotubes include carbon nanotubes manufactured by Meijo Nano Carbon Co., Ltd.; NTP3003, NTP3021, NTP3121, NTP8012, NTP8022, NTP9012, NTP9112, and the like manufactured by NTP Co., Ltd.; and TUBALL manufactured by OCSiAl Corporation. Commercially available graphene-based carbons include, but are not limited to, graphene nanoplatelets xGnP-C-300, xGnP-C-500, xGnP-C-750, xGnP-M-5, xGnP-M-15, xGnP-M-25, xGnP-H-5, xGnP-H-15, and xGnP-H-25 manufactured by XG Sciences. Among these, graphite is preferred as a commercially available carbonaceous raw material from the viewpoints of electrical conductivity and cost.

[0045] As the carbonaceous raw material for producing the boron-containing carbon material in the present invention, not only inorganic carbonaceous raw materials but also organic carbonaceous raw materials that become carbon particles after heat treatment can be used. Specific organic materials include phenolic resins, polyimide resins, polyamide resins, polyamideimide resins, polyacrylonitrile resins, polyaniline resins, Examples of the resin include phenol formaldehyde resins, polyimidazole resins, polypyrrole resins, polybenzimidazole resins, melamine resins, pitch, coke, lignite, polycarbodiimide, biomass, protein, humic acid, and derivatives thereof. Among these, it is preferable to use coke and pitch, which are also used as raw materials for graphite.

[0046] <Boron-containing compounds> Next, a compound containing boron used in the production of a boron-containing carbon material will be described. The compound containing boron is not particularly limited, but examples thereof include boron carbide, boron oxide, boron nitride, metal borides, boron oxoacids, boranes, and boron-containing organic compounds. Specifically, in boron carbide, B4C(B 12 C3), B 12Examples of boron oxyacids include orthoboric acid, metaboric acid, tetraboric acid, and the like; boranes include monoborane, diborane, decaborane, and the like; boron-containing organic compounds include boric acid esters such as trimethyl borate and triethyl borate, substituted boranes such as triethylborane and triphenylborane, and boronic acids such as phenylboronic acid and phenylboronic acid esters.

[0047] <Resin composition> The boron-containing carbon material of the present invention can be used in the form of a resin composition containing the boron-containing carbon material and a resin component. Examples of the resin component include a binder resin and a resin-type dispersant. The binder resin can include one or more types selected from the group consisting of polyurethane resins, polyamide resins, acrylonitrile resins, acrylic resins, butadiene resins, polyvinyl resins, polyvinyl butyral resins, polyolefin resins, polyester resins, polystyrene resins, EVA resins, polyvinylidene fluoride resins, polytetrafluoroethylene resins, silicone resins, polyether resins, cellulose resins such as carboxymethyl cellulose, and the like. However, the binder resin is not limited to these resins. The binder resin may be used alone or in combination of two or more. As the binder resin, a non-fluoride resin is preferable from the viewpoints of cost and adhesion.

[0048] The binder resin may be a curable resin that undergoes a curing (crosslinking) reaction after the binder resin is applied to a substrate. The binder resin may be a soluble resin that dissolves in an aqueous or non-aqueous solvent or a dispersion-type resin fine particle. Dispersion-type resin fine particles are resin fine particles that do not dissolve in an aqueous or non-aqueous dispersion medium and exist in the form of fine particles, and the dispersion is generally called an emulsion. These may be used alone or in combination of two or more.

[0049] The particle structure of the dispersion type resin fine particles may be a multi-layer structure such as a core-shell particle. For example, by localizing a resin obtained by mainly polymerizing a monomer having a functional group in the core or shell, or by providing a difference in Tg or composition between the core and the shell, the curability, drying property, film-forming property, and mechanical strength of the binder can be improved. From the viewpoint of binding property and particle stability, the average particle size of the resin fine particles is preferably 10 to 1000 nm, and more preferably 10 to 300 nm. In addition, since the stability of the particles may be impaired if a large amount of coarse particles exceeding 1 μm is contained, it is preferable that the amount of coarse particles exceeding 1 μm is at most 5% or less. In the present invention, the average particle size refers to the volume average particle size, and can be measured by the dynamic light scattering method as follows. First, the resin fine particles are diluted 200 to 1000 times with the same dispersion liquid as the dispersion medium according to the solid content. Next, about 5 ml of the diluted dispersion liquid is poured into the cell of a measuring device (Nanotrack manufactured by Nikkiso Co., Ltd.), and the dispersion medium and resin refractive index conditions according to the sample are input, and then measurement is performed. The volume particle size distribution data (histogram) obtained at this time can be used to measure the particle size distribution.

[0050] The dispersed resin particles preferably contain crosslinked resin particles. The crosslinked resin particles refer to resin particles having an internal crosslinked structure (three-dimensional crosslinked structure), and it is important that the particles are crosslinked inside. From the viewpoint of the slurry stability and coatability of the resin composition, it is preferable to use a water-soluble resin and aqueous resin particles in combination.

[0051] (Water-soluble resin) A water-soluble resin is a resin that can be completely dissolved in water without separation or precipitation after 1 g of the resin is added to 99 g of water at 25° C., stirred, and left for 24 hours at 25° C. Water-soluble resins have the effect of increasing the dispersibility of carbon materials, so a stable composition can be obtained with a small amount of resin. Water-soluble resins are broadly classified into anionic resins, cationic resins, amphoteric resins having both anionic and cationic properties, and nonionic resins other than those, and further, the resins may be composed of multiple monomers. Moreover, the water-soluble resins may be used alone or in combination of two or more kinds.

[0052] Examples of anionic resins include resins containing a skeleton containing a carboxyl group, a sulfo group, a phosphoric acid group, or a partially or completely neutralized skeleton thereof. Examples of such resins include homopolymers of polymerizable monomers such as (meth)acrylic acid, itaconic acid, fumaric acid, maleic acid, 2-sulfoethyl methacrylate, and 2-methacryloyloxyethyl acid phosphate, copolymers thereof with other polymerizable monomers, carboxymethyl cellulose, and alkali neutralized products thereof.

[0053] Examples of cationic resins include resins containing a cyclic amino group, a skeleton in which the amino group is partially or completely neutralized, and quaternary ammonium salts. Examples of the resins include homopolymers of polymerizable monomers such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethyl (meth)acrylate, and vinylpyridine, copolymers with other polymerizable monomers, and acid-neutralized products thereof.

[0054] Examples of amphoteric resins include resins containing both the anionic skeleton and the cationic skeleton, such as copolymers of styrene, maleic acid, and N,N-dimethylaminoethyl (meth)acrylate. The nonionic resin is a resin other than the anionic, cationic and amphoteric resins. Examples of the nonionic resin include polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl butyral, polyacrylamide, poly-N-vinylacetamide, polyalkylene glycol, etc.

[0055] The molecular weight of the water-soluble resin is not particularly limited, but the mass average molecular weight is preferably 5,000 to 2,500,000. The mass average molecular weight (Mw) refers to the molecular weight calculated as polyethylene oxide by gel permeation chromatography (GPC).

[0056] (Aqueous resin fine particles) The aqueous resin particles are dispersion-type resin particles in which the resin does not dissolve in water but exists in the form of fine particles, and are also called water-dispersed resin particles. The aqueous dispersion is generally called an aqueous emulsion. Examples of aqueous resin particles include (meth)acrylic emulsions, nitrile emulsions, urethane emulsions, polyolefin emulsions, fluorine emulsions (polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), etc.), diene emulsions (styrene-butadiene rubber (SBR), etc.), etc. Note that (meth)acrylic means methacrylic or acrylic. When a coating film is formed from a resin composition containing aqueous resin microparticles, the resin composition has excellent adhesion between particles and to a substrate, and can provide a coating film with high strength. Furthermore, because of the excellent adhesion, only a small amount of aqueous resin microparticles is required, and as a result, the electrical conductivity of the resin composition is improved. In order to obtain the above-mentioned effects, the aqueous resin microparticles are preferably (meth)acrylic emulsions or urethane emulsions, which have excellent interparticle adhesion and flexibility (film flexibility).

[0057] The (meth)acrylic emulsion is an emulsion polymer containing 10 parts by mass or more of a monomer having a (meth)acryloyl group, preferably 20 parts by mass or more, more preferably 30 parts by mass or more. The monomer having an acryloyl group has excellent reactivity, so that resin microparticles can be relatively easily produced. Therefore, the (meth)acrylic emulsion is particularly preferable as the aqueous resin microparticle.

[0058] <Solvent (dispersion medium)> When the carbon material and the binder are mixed uniformly, a solvent can be appropriately used. Such a solvent is not particularly limited as long as it can dissolve the resin or stably disperse the resin fine particle emulsion, and examples of the solvent include water and organic solvents.

[0059] The organic solvent may be any suitable one selected from among alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol methyl ether, diethylene glycol methyl ether, etc.; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ethers such as tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, etc.; hydrocarbons such as hexane, heptane, octane, etc.; aromatics such as benzene, toluene, xylene, cumene, etc.; esters such as ethyl acetate, butyl acetate, etc., depending on the composition of the resin composition. The solvent may be water and an organic solvent, or two or more organic solvents may be used.

[0060] When using a water-soluble resin or aqueous resin particles, it is preferable to use water as a solvent from the viewpoint of solubility and dispersibility, and a liquid medium compatible with water may be added as necessary. As the liquid medium compatible with water, an alcohol-based solvent having a carbon number of 4 or less is preferable. In addition, various additives such as ultraviolet absorbers, ultraviolet stabilizers, radical scavengers, fillers, thixotropy-imparting agents, antiaging agents, antioxidants, antistatic agents, flame retardants, thermal conductivity improvers, plasticizers, anti-sagging agents, antifouling agents, preservatives, bactericides, defoamers, leveling agents, antiblocking agents, curing agents, thickeners, dispersants, and silane coupling agents may be added to the resin composition of the present invention, if necessary, within a range that does not impair the effects of the present invention.

[0061] The resin composition of the present invention may be formed by melt-kneading the boron-containing carbon material and a thermoplastic resin or a thermosetting resin. Examples of thermoplastic resins include polyolefins, polystyrene, polyvinyl chloride, polyvinyl alcohol, polyvinylidene chloride, polyethylene terephthalate, polycarbonate, acrylonitrile-butadiene-styrene, polymethyl methacryl, polyamide, polyphenylene ether, polybutylene terephthalate, polysulfone, polyethersulfone, polyphenylene sulfide, polyarylate, polyamideimide, polyetherimide, polyetheretherketone, polyimide, polytetrafluoroethylene, and polyvinylidene fluoride. Examples of the thermosetting resin include phenol, urea, melamine, unsaturated polyester, epoxy, silicone, and polyurethane. These may be used alone or in combination. When using a plurality of resins, for example, a sea-island structure may be formed by combining polyethylene terephthalate and a polyolefin resin. By forming a sea-island structure, the amount of carbon material required to exhibit electrical conductivity can be reduced, which is preferable.

[0062] <Conductive assistant> The resin composition of the present invention may further contain a conductive assistant (excluding the boron-containing carbon material of the present invention) as necessary. Examples of the conductive assistant include carbon assistants such as carbon black, activated carbon, graphite, conductive carbon fibers (carbon nanotubes, carbon nanofibers, etc.), carbon nanohorns, graphene, graphene nanoplatelets, and nanoporous carbon, and metal assistants such as metal nanoparticles (silver, copper, etc.). The conductive assistant preferably contains boron, and may be doped with boron. When the conductive assistant contains boron, the content of boron in the conductive assistant is preferably 0.01 to 2 mol%, more preferably 0.1 to 1.1 mol%. When the content of boron in the conductive assistant is 0.01 to 2 mol%, the wettability to the solvent and the binder resin is improved, and the hardness of the conductive assistant is increased. This improves the dispersibility of the resin composition and the durability against external forces such as impact, and improves the dispersion stability and film strength.

[0063] From the viewpoint of specific surface area and particle size, the conductive assistant is preferably carbon black. Note that, as the carbon assistant, the carbon black, activated carbon, graphite, conductive carbon fiber (carbon nanotube, carbon nanofiber, etc.), carbon nanohorn, graphene, graphene nanoplatelet, and nanoporous carbon described above can be used.

[0064] The pore volume of the conductive assistant is preferably 0.1 to 5 cm 3 / g, more preferably 0.2 to 3 cm 3 / g, and more preferably 0.5 to 1.8 cm 3 / g. The pore volume is 0.1 to 5 cm 3 / g range, the resin composition will have excellent dispersibility and durability. In the present invention, the pore volume means the total pore volume per unit mass of a sample, and can be measured by the method described below.

[0065] The conductive assistant preferably has at least mesopores or macropores. Pores are called different names depending on the size of their diameter, and are classified by IUPAC into three classes: micropores with a pore diameter of less than 2 nm, mesopores with a pore diameter of 2 to 50 nm, and macropores with a pore diameter of more than 50 nm. The peak pore diameter can be determined by the method described below.

[0066] The pore diameter and pore volume can be determined by a nitrogen adsorption method, etc. In the nitrogen adsorption method, an adsorption isotherm is measured by making an adsorbent adsorb and desorb nitrogen as an adsorbed molecule, and the measured data is analyzed to calculate the specific surface area, pore volume, and pore diameter. More specifically, the specific surface area is determined by the BET method. The pore volume and pore diameter are determined by the BJH method, which is a widely used pore distribution analysis method. By using the BJH method, the pore distribution of 2 to 200 nm can be plotted, and the presence of mesopores or macropores can be confirmed. The peak pore size can be calculated, for example, by plotting the logarithmic differential pore volume against the pore size and determining from a peak obtained in the range of 2 to 200 nm. Other measuring methods that can be used include mercury intrusion porosimetry and bubble point method.

[0067] The proportion of the boron-containing carbon material in the total solid content of the resin composition is preferably 60 to 95 mass %, more preferably 75 to 90 mass %. When the carbon material is 60 mass % or more, contact between the carbon materials in the conductive film increases, and good conductivity is obtained. On the other hand, when the carbon material is 95 mass % or less, durability such as adhesion of the conductive film is not decreased, so this is preferable.

[0068] When the resin composition further contains a conductive assistant, the proportion of the boron-containing carbon material of the present invention in the total solid content of the resin composition is preferably 40 to 80 mass%, more preferably 45 to 70 mass%, and even more preferably 50 to 60 mass%. On the other hand, the proportion of the conductive assistant in the total solid content of the resin composition is preferably 1 to 40 mass %, more preferably 5 to 30 mass %, and further preferably 10 to 20 mass %.

[0069] The viscosity of the resin composition can be appropriately adjusted by the method of applying the resin composition, but is generally preferably 10 mPa·s or more and 30,000 mPa·s or less. The viscosity can be measured, for example, using a B-type viscometer. The viscosity of a dispersion containing a boron-containing carbon additive as a conductive additive tends to be lower than that of a dispersion prepared using a carbon additive that does not contain boron, due to the change in the surface state of the carbon additive as described above, and this has the effect of making the dispersion easier to handle.

[0070] (Dispersing machine / mixing machine) As an apparatus used in obtaining the resin composition, a disperser or mixer that is generally used for dispersing pigments or the like can be used. Examples of such dispersing and mixing machines include mixers such as a Disper, Homomixer, or Planetary Mixer; homogenizers such as M-Technique's "Clearmix" or PRIMIX's "Filmix"; media-type dispersing machines such as a paint conditioner (Red Devil), ball mill, sand mill (Shinmaru Enterprises' "Dynomill", etc.), attritor, pearl mill (Eirich's "DCP Mill", etc.), or Coball mill; media-less dispersing machines such as wet jet mills (Zenus PY, Sugino Machine's "Starburst", Nanomizer, Nanomizer, etc.), M-Technique's "Clear SS-5", or Nara Machine's "MICROS"; or other roll mills, kneaders, and ultrasonic dispersing machines, but are not limited to these.

[0071] For example, when using a media type disperser, it is preferable to use a method using a disperser whose agitator and vessel are made of ceramic or resin, or a disperser whose metallic agitator and vessel surface are treated with tungsten carbide spraying or resin coating, etc. As the media, it is preferable to use glass beads, or ceramic beads such as zirconia beads or alumina beads. Only one type of dispersing device may be used, or multiple types of devices may be used in combination.

[0072] <Conductive film> The conductive film of the present invention is a film formed from a resin composition, and can be formed by applying the resin composition onto a substrate and drying it as necessary.

[0073] (base material) The shape of the substrate used for forming the conductive film is not particularly limited and may be appropriately selected according to the application. The substrate is preferably in the form of a sheet, more preferably an insulating resin film. The material of the substrate is not particularly limited, and examples thereof include PET (polyethylene terephthalate), PEN (polyethylene naphthalate), polyimide, polyvinyl chloride, polyamide, nylon, OPP (oriented polypropylene), and CPP (unoriented polypropylene).

[0074] Regarding the shape, a flat film is generally used, but substrates with a roughened surface, those treated with a primer, those with holes, and those in a mesh shape can also be used.

[0075] The method of applying the resin composition on the substrate is not particularly limited, and any known method can be used. Examples of such application methods include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting. Examples of drying methods include, but are not limited to, standing drying, blowing drying, hot air drying, infrared heating, and far infrared heating.

[0076] After coating, the conductive film may be rolled using a lithographic press or a calendar roll, and the rolling may be performed while heating in order to soften the conductive film and make it easier to press. The thickness of the conductive film is generally 0.1 μm or more and 1 mm or less, and preferably 1 μm or more and 200 μm or less.

[0077] (Volume resistivity of conductive film) The volume resistivity of the conductive film of the present invention is preferably 5×10 -3 Ω cm, preferably less than 3×10 -3 Ω cm, and more preferably less than 2×10 -3 The volume resistivity is less than 5×10 -3 With a resistivity of less than Ω·cm, this composition has extremely high conductivity and can be used for battery electrodes, current collectors, batteries, wiring in electronic devices, etc. EXAMPLES

[0078] The present invention will be described in more detail below with reference to examples, but the following examples are not intended to limit the scope of the invention. In the examples and comparative examples, "parts" means "parts by mass" and "%" means "% by mass".

[0079] <Production of boron-containing carbon materials> [Example 1] Exfoliated graphite UP-20 (manufactured by Nippon Graphite Industries Co., Ltd.) and boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 79 / 21 (exfoliated graphite / boric acid), and mixed and composited using a particle compositer Mechanofusion (manufactured by Hosokawa Micron Corporation) to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a firing furnace under an argon atmosphere at 2050°C for 1 hour to obtain a carbon material (1).

[0080] [Example 2] Spheroidized graphite CGB-50 (manufactured by Nippon Graphite Industries Co., Ltd.), boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and ethanol were weighed out to a mass ratio of 79 / 21 / 300 (spheroidized graphite / boric acid / ethanol), mixed with a disperser, dried in an oven at 80°C under atmospheric pressure, and then mixed and composited with a particle compositer Mechanofusion (manufactured by Hosokawa Micron Corporation) to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a firing furnace under an argon atmosphere at 2050°C for 1 hour to obtain carbon material (2).

[0081] [Examples 3 to 8] Carbon materials (3) to (8) were obtained in the same manner as in Example 1 using the compounds containing carbon and boron shown in Table 1.

[0082] [Comparative Example 1] Spheroidal graphite CGB-50 (manufactured by Nippon Graphite Co., Ltd.) was filled into a graphite crucible and heat-treated in a firing furnace under an argon atmosphere at 2050° C. for 1 hour to obtain a carbon material (9).

[0083] [Comparative Example 2] Multi-walled carbon nanotubes (MWCNT) NTP3003 (NTP) and boric acid (Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 99 / 1 (MWCNT / boric acid) and mixed in a mortar to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a firing furnace under an argon atmosphere at 1800°C for 1 hour to obtain a carbon material (10).

[0084] [Comparative Example 3] Graphene nanoplatelets (GNP) xGnP-C-750 (manufactured by XG Sciences) and boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 99 / 1 (GNP / boric acid) and mixed in a mortar to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a firing furnace under an argon atmosphere at 2050°C for 1 hour to obtain a carbon material (11).

[0085] <Evaluation of boron-containing carbon materials> The physical properties of the prepared boron-containing carbon material were evaluated by the following methods. The results are shown in Table 1.

[0086] (Boron content in carbon material) The boron content in the carbon material was measured using an ICP emission spectrometer (SPECTROARCOS FHS12 manufactured by SPECTRO Inc.) The obtained value indicates the amount of boron contained in the entire carbon material.

[0087] (Content of boron element and substitutional boron element on the surface of carbon material) The evaluation was performed using an X-ray photoelectron spectrometer, ThermoFisher Scientific K-Alpha. The ratio (mol%) of all surface boron elements was calculated from the total spectral area obtained from the boron B1s spectrum peak. In addition, the ratio (mol%) of surface substitutional boron elements was calculated from the ratio of the peak area of ​​188 to 189.3 eV to the total spectral area of ​​boron.

[0088] (pyrolysis temperature) The thermal decomposition temperature was evaluated using a differential thermobalance, Thermo plus EV02 TG8121, manufactured by Rigaku. Compressed air was flowed at 200 mL / min, and the thermal decomposition temperature was used when the temperature was increased from 40°C to 1000°C at 10°C / min. The thermal decomposition temperature was calculated as shown in Figure 1, for example, by reading the rise of the largest exothermic peak (A in Figure 1) and the top of the largest exothermic peak (B in Figure 1) in the DTA curve obtained by measurement, and finding the intersection point (C in Figure 1) extrapolated from the slope at the corresponding points (A', B' in Figure 1) of the TG curve.

[0089] (Volume resistivity) The volume resistivity was evaluated using a powder resistivity measurement system MCP-PD51 manufactured by Mitsubishi Chemical Analytech Co., Ltd. Measurements were performed using a four-point probe method with a low-resistance powder probe, and the volume resistivity value was used when a load of 20 kN was applied to each sample.

[0090] [Table 1]

[0091] It is clear from Table 1 that by controlling the boron content in the carbon material and the pyrolysis temperature within the ranges of the present invention, very good electrical conductivity can be achieved.

[0092] <Production of binder resin> [Production Example 1] Polyurethane resin solution A reaction vessel equipped with a stirrer, thermometer, reflux condenser, dropping device, and nitrogen inlet tube was charged with 455.5 parts of a polyester polyol obtained from terephthalic acid, adipic acid, and 3-methyl-1,5-pentanediol ("Kuraray Polyol P-2011" manufactured by Kuraray Co., Ltd., Mn=2,011), 16.5 parts of dimethylolbutanoic acid, 105.2 parts of isophorone diisocyanate, and 140 parts of toluene, and reacted at 90°C for 3 hours under a nitrogen atmosphere, and 360 parts of toluene was added to this to obtain a urethane prepolymer solution having isocyanate groups. Next, 969.5 parts of the obtained urethane prepolymer solution having isocyanate groups was added to a mixture of 19.9 parts of isophorone diamine, 0.63 parts of di-n-butylamine, 294.5 parts of 2-propanol, and 335.5 parts of toluene (the total equivalent of amino groups relative to the free isocyanate groups at both ends of the urethane prepolymer was 0.98), and the mixture was reacted for 3 hours at 50° C., and then for 2 hours at 70° C. The mixture was then diluted with 126 parts of toluene and 54 parts of 2-propanol to obtain a polyurethane resin solution having a weight average molecular weight of 61,000 and an acid value of 10 mgKOH / g. The obtained polyurethane resin solution was diluted with toluene / methyl ethyl ketone / 2-propanol (mass ratio: 1 / 1 / 1) to obtain a polyurethane resin solution with a solid content of 20 mass %.

[0093] [Production Example 2] Polyamide resin solution In a four-neck flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, an inlet tube, and a thermometer, 156.2 parts of Pripol 1009 (hydrogenated dimer acid, Croda Japan Co., Ltd.) as a polybasic acid compound, 5.5 parts of 5-hydroxyisophthalic acid, 146.4 parts of Priamine 1074 (Croda Japan Co., Ltd.) as a polyamine compound, and 100 parts of ion-exchanged water were charged and stirred until the temperature of the heat generation became constant. When the temperature stabilized, the temperature was raised to 110°C, and after confirming the outflow of water, the temperature was raised to 120°C after 30 minutes, and then the dehydration reaction was continued while raising the temperature by 10°C every 30 minutes. After the temperature reached 230°C, the reaction was continued at that temperature for 3 hours, and the temperature was lowered by holding it under a vacuum of about 2 kPa for 1 hour. Finally, an antioxidant was added to obtain a polyamide resin having a weight average molecular weight of 24,000, an acid value of 13.2 mgKOH / g, a hydroxyl value of 5.5 mgKOH / g, and a glass transition temperature of -32°C. The obtained polyamide resin was diluted with toluene / 2-propanol (mass ratio: 2 / 1) to obtain a polyamide resin solution with a solid content of 20 mass %.

[0094] [Production Example 3] Polyester resin solution Vylon 200 (polyester resin, manufactured by Toyobo Co., Ltd.) was diluted with toluene / methyl ethyl ketone (mass ratio: 1 / 1) to obtain a polyester resin solution with a solid content of 20 mass %.

[0095] The resins were evaluated as follows. (Weight average molecular weight (Mw)) The weight average molecular weight was measured using a gel permeation chromatography (GPC) "HPC-8020" manufactured by Tosoh Corporation. GPC is a liquid chromatography that separates and quantifies substances dissolved in a solvent (THF; tetrahydrofuran) based on the difference in their molecular size. The measurement in the present invention was performed using two "LF-604" columns (manufactured by Showa Denko K.K.: GPC column for rapid analysis: 6 mm ID x 150 mm size) connected in series, at a flow rate of 0.6 ml / min and a column temperature of 40°C, and the weight average molecular weight was determined in polystyrene equivalent.

[0096] (Acid Value (AV)) Approximately 1 g of sample was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 ml of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture was added to dissolve it. Phenolphthalein test solution was added as an indicator and the mixture was allowed to stand for 30 seconds. After that, the solution was titrated with 0.1 N alcoholic potassium hydroxide solution until it turned a light pink color, and the acid value was calculated using the following formula. Acid value (mgKOH / g)=(5.611×a×F) / S however, S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic potassium hydroxide solution (ml) F: Potency of 0.1N alcoholic potassium hydroxide solution

[0097] (Hydroxyl Value (OHV)) The hydroxyl value is the amount of hydroxyl groups contained in 1 g of the hydroxyl-containing resin, expressed as the amount (mg) of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl groups when the hydroxyl groups are acetylated. The hydroxyl value was measured according to JIS K0070, and in the present invention, it was calculated taking into account the acid value as shown in the following formula. Approximately 1 g of sample was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 ml of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture was added and dissolved. Exactly 5 ml of an acetylating agent (a solution of 25 g of acetic anhydride dissolved in pyridine to a volume of 100 ml) was then added and stirred for approximately 1 hour. Phenolphthalein test solution was added as an indicator and allowed to stand for 30 seconds. After that, the solution was titrated with 0.1 N alcoholic potassium hydroxide solution until it turned a light pink color, and the hydroxyl value was calculated using the following formula. Hydroxyl value (mgKOH / g) = [{(ba) × F × 28.05} / S] + D however, S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic potassium hydroxide solution (ml) b: Amount of 0.1N alcoholic potassium hydroxide solution consumed in the blank experiment (ml) F: Potency of 0.1N alcoholic potassium hydroxide solution D: Acid value (mgKOH / g)

[0098] (Glass transition temperature (Tg)) The glass transition temperature of the resin was measured by drying and removing the solvent from the resin and heating it from -80 to 150°C at a rate of 2°C / min using a Mettler Toledo DSC-1.

[0099] <Production of boron-containing conductive additive> [Production example 4] CB(2) 92 parts of EC-600JD (Ketjen Black, Lion Specialty Chemicals) and 8 parts of boric acid (Fujifilm Wako Pure Chemicals) were mixed with 800 parts of toluene and 100 parts of ethanol as solvents, mixed in a planetary centrifugal mixer, and dried in an oven at 80°C under atmospheric conditions to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 1700°C for 1 hour to obtain CB(2). The pore volume values ​​are shown in Table 2. The boron content of CB(2) was 0.73 mol%. The boron content was measured in the carbon material using ICP emission spectroscopy (SPECTROARCOS FHS12, manufactured by SPECTRO). The thermal decomposition temperature was less than 700°C.

[0100] [Production example 5] CB(3) CB(3) was obtained in the same manner as in Production Example 4, except that EC-600JD was replaced with EC-300J (Ketjen Black, manufactured by Lion Specialty Chemicals). The boron content of CB(3) was 0.71 mol%. The thermal decomposition temperature was less than 700°C.

[0101] [Manufacturing example 6] CB(4) CB(4) was obtained in the same manner as in Production Example 4, except that the amount of EC-600JD added was 80 parts, the amount of boric acid was 20 parts, and the heat treatment temperature was changed to 2000°C. The boron content of CB(4) was 2.24 mol%. The thermal decomposition temperature was less than 700°C.

[0102] [Production example 7] CNT(2) CNT (2) was obtained in the same manner as in Production Example 4, except that EC-600JD was replaced with multi-walled CNT K-Nanos 100T (Kumho Petrochemical Co., Ltd.). The boron content of CNT (2) was 0.69 mol%. The thermal decomposition temperature was less than 700°C.

[0103] <Production of resin composition and conductive film> [Example A1] 87 parts of carbon material (7), 65 parts of polyester resin solution (13 parts of resin solid content) as binder resin, and 170 parts of toluene / methyl ethyl ketone / 2-propanol (mass ratio: 1 / 1 / 1) as solvent were mixed in a mixer, and further dispersed in a sand mill to obtain a resin composition (1). Next, this resin composition (1) was applied onto a PET film substrate having a thickness of 100 μm using a doctor blade, and then dried in an oven. Then, roll pressing was performed under a linear pressure of 300 kg / cm to obtain a conductive film (1).

[0104] [Examples A2 to A4, Comparative Examples A1 to A3] Resin compositions (2) to (7) and conductive films (2) to (7) were obtained in the same manner as in Example A1, except that the blending compositions were changed as shown in Table 2.

[0105] [Example A5] 56 parts of carbon material (7), 14 parts of CB (1) as a conductive assistant, 150 parts of polyurethane resin solution (resin solid content 30 parts) as a binder resin, and toluene / methyl ethyl ketone / 2-propanol (mass ratio: 1 / 1 / 1) as a solvent were mixed in a mixer so that the solid content in the composition was 30 mass%, and further dispersed in a sand mill to obtain a resin composition (8). Next, this resin composition (8) was applied to a PET film substrate with a thickness of 100 μm using a doctor blade, and then dried in an oven to obtain a conductive film (8).

[0106] [Examples A6 to A17, A19, A20, Comparative Examples A4 to A6] Resin compositions (9) to (20), (22) to (26) and conductive films (9) to (20), (22) to (26) were obtained in the same manner as in Example A5, except that the blending compositions were changed to those shown in Table 2.

[0107] [Example A18] 56 parts of the carbon material (1), 19 parts of CB (5) (acetylene black HS-100, manufactured by Denka Co., Ltd.) as a conductive assistant, and 250 parts of an aqueous solution (resin solid content: 5 parts) in which 2% by mass of water-soluble resin CMC (carboxymethylcellulose #1240, manufactured by Daicel Miraize Co., Ltd.) as a binder resin was dissolved were mixed in a mixer and further dispersed in a sand mill. Next, 40 parts (resin solid content 20 parts) of aqueous resin fine particles (Polyacrylic emulsion W-168, manufactured by Toyochem Co., Ltd., solid content 50% by mass) as a binder resin were added and mixed with a mixer to obtain a resin composition (21). Next, this resin composition (21) was applied onto a PET film substrate having a thickness of 100 μm using a doctor blade, and then dried in an oven to obtain a conductive film (21).

[0108] <Evaluation of resin composition and conductive film> The obtained resin compositions and conductive films were evaluated by the following methods. The evaluation results are shown in Table 2.

[0109] [Dispersion stability evaluation] The dispersion stability was evaluated based on the change in liquid properties after the resin composition was left to stand for 7 days at 25° C. The change in liquid properties was judged based on the ease of stirring when stirred with a spatula. Judgment criteria ○: No change in liquid properties (good) △: Viscosity has increased, but gelation has not occurred (passable) ×: Gelled (bad)

[0110] [Coatability evaluation] The obtained conductive film was observed at 500 times magnification using a video microscope VHX-900 (manufactured by Keyence Corporation), and coating unevenness and pinholes were judged according to the following criteria. Coating unevenness was judged based on the shading of the film surface. Pinholes were judged based on the presence or absence of uncoated defects in the film. <<Uneven coating>> ○: No shading on the film surface is observed (good) △: There are 2 to 3 areas of shading on the film surface, but these are very small areas (OK) ×: Many shading patterns are observed on the film surface, or one or more shading stripes with a length of 5 mm or more are observed (defective). "Pinhole" ○: No pinholes found (good) △: There are 2 to 3 pinholes, but they are extremely small (passable) ×: Many pinholes are found, or one or more pinholes with a diameter of 1 mm or more are found (defective).

[0111] [Volume resistivity of film] The volume resistivity of the conductive film was measured by a four-terminal method using Loresta GP (manufactured by Nitto Seiko Analytech Co., Ltd.) in accordance with JIS-K7194.

[0112] [Film durability] The durability of the conductive film was evaluated by scratch hardness (pencil method) using an HB pencil in accordance with JIS K5600-5-4:1999. ○: No plastic deformation or cohesive failure occurs (good) △: Plastic deformation or cohesive failure has partially occurred (OK) ×: Plastic deformation and cohesive failure occurred (bad)

[0113] [Table 2]

[0114] According to the results in Table 2, the resin composition using the boron-containing carbon material of the present invention has excellent dispersion stability and coatability, and the conductive film formed from the resin composition has both high conductivity and durability. In addition, by comparing Examples A1 to A4, it was found that the difference in the boron content of the carbon material has a large effect on the properties of the resin composition and the conductive film. On the other hand, focusing on the conductive assistant, a comparison of Examples A6, A13 to A16 revealed that the dispersion stability, coatability and conductive film properties of the resin composition differ depending on the composition ratio of the conductive assistant in the resin composition. In addition, a comparison of Examples A7, A10, A11 and A17 revealed that the dispersion stability, coatability and conductive film properties of the resin composition differ depending on the pore volume of the conductive assistant in the resin composition. In addition, a comparison of Examples A10 and A12 revealed that the boron content of the conductive assistant also affects the coatability of the resin composition and the properties of the conductive film. Therefore, these results suggest that factors other than the conductivity caused by the boron-containing carbon material are involved. Although the details are unclear at this stage, the resin composition of the present invention is presumed to exhibit excellent conductivity by efficiently forming a conductive network of the carbon material in the film, since the boron-containing carbon material itself not only has excellent conductivity, but also has good dispersibility and dispersion stability, and further has good coatability. It is also presumed that the uniform network of the carbon material also leads to improved durability of the conductive film. In addition, the boron-containing carbon material of the present invention not only has improved wettability with respect to solvents and binder resins, but also tends to have a higher hardness, which is thought to affect dispersibility and coatability. It is considered that this is why the resin composition containing the boron-containing carbon material has improved dispersibility and coatability and exhibits excellent electrical conductivity. [Explanation of symbols]

[0115] A: The point where the largest exothermic peak occurs in the DTA curve A': The point on the TG curve corresponding to the onset of the largest exothermic peak in the DTA curve B: The top of the largest exothermic peak in the DTA curve B': The point on the TG curve corresponding to the largest exothermic peak top on the DTA curve C: Intersection point extrapolated from the slopes at A' and B' (thermal decomposition temperature)

Claims

1. A boron-containing carbon material is doped with boron element so as to substitute at least a part of the carbon element in a carbon skeleton, the boron-containing carbon material having a thermal decomposition temperature in an oxygen atmosphere of 800°C or higher and lower than 900°C, and a content of boron element in the carbon material of 0.005 to 15 mol%.

2. 2. The boron-containing carbon material according to claim 1, wherein the content of boron element on the surface of the carbon material is 0.01 to 10 mol %.

3. 3. The boron-containing carbon material according to claim 1, comprising at least one selected from the group consisting of graphite-based carbon materials, graphene-based carbon materials, and carbon nanotube-based carbon materials.

4. 4. The boron-containing carbon material according to claim 1, wherein the content of boron element on the surface of the carbon material is 0.01 to 1 mol %.

5. A resin composition comprising the carbon material according to any one of claims 1 to 4 and a resin component.

6. The resin composition according to claim 5 , further comprising a conductive assistant.

7. The pore volume of the conductive assistant is 0.1 to 5 cm 3 The resin composition according to claim 6, wherein the molecular weight is 1 / g.

8. A conductive film formed from the resin composition according to any one of claims 5 to 7.

9. A method for producing a boron-containing carbon material, in which boron element is doped to replace at least a portion of the carbon element in the carbon skeleton, the thermal decomposition temperature in an oxygen atmosphere is 800°C or higher and lower than 900°C, and the content of boron element in the carbon material is 0.005 to 15 mol%, comprising the steps of mixing exfoliated graphite or spheroidized graphite with a compound containing boron to obtain a mixture, and heat-treating the mixture at 1800°C to 3000°C.

Citation Information

Patent Citations

  • Graphite material for high-capacity nonaqueous secondary battery negative electrode and its manufacture

    JP1998255799A

  • Production of carbon nanotube containing boron

    JP2000281323A

  • Sic-c / c composite material, its use, and production thereof

    JP2000351672A

  • Graphite material containing boron, method of manufacturing it, and lithium ion secondary cell

    JP2002220218A

  • Carbon nanotube

    JP2006240932A